Insidious Risk of Severe Mycobacterium chimaera Infection in Cardiac Surgery Patients. (7th December 2016) - Chand, Meera; Lamagni, Theresa; Kranzer, Katharina; Hedge, Jessica; Moore, Ginny; Parks, Simon; Collins, Samuel; del Ojo Elias, Carlos; Ahmed, Nada; Brown, Tim; Smith, E. Grace; Hoffman, Peter; et al.
Summary: A low but increasing risk of invasive Mycobacterium chimaera infection was identified in cardiothoracic patients. A mechanism for transmission in surgery was identified and, coupled with genome sequencing, provides new evidence supporting a causal relationship between contaminated heater-coolers and infection. Abstract: Background: An urgent UK investigation was launched to assess risk of invasive Mycobacterium chimaera infection in cardiothoracic surgery and a possible association with cardiopulmonary bypass heater-cooler units following alerts in Switzerland and The Netherlands. Methods: Parallel investigations were pursued: (1) identification of cardiopulmonary bypass–associated M. chimaera infection through national laboratory and hospital admissions data linkage; (2) cohort study to assess patient risk; (3) microbiological and aerobiological investigations of heater-coolers in situ and under controlled laboratory conditions; and (4) whole-genome sequencing of clinical and environmental isolates. Results: Eighteen probable cases of cardiopulmonary bypass–associated M. chimaera infection were identified; all except one occurred in adults. Patients had undergone valve replacement in 11 hospitals between 2007 and 2015, a median of 19 months prior to onset (range, 3 months to 5 years). Risk to patients increased after 2010 from <0.2 to 1.65 per 10000 person-years in 2013, a 9-fold rise for infections within 2 years of surgery (rate ratio, 9.08 [95% CI, 1.81–87.76]). Endocarditis was the most common presentation (n = 11). To date, 9 patients have died. Investigations identified aerosol release through breaches in heater-cooler tanks. Mycobacterium chimaera and other pathogens were recovered from water and air samples. Phylogenetic analysis found close clustering of strains from probable cases. Conclusions: We identified low but escalating risk of severe M. chimaera infection associated with heater-coolers with cases in a quarter of cardiothoracic centers. Our investigations strengthen etiological evidence for the role of heater-coolers in transmission and raise the possibility of an ongoing, international point-source outbreak. Active management of heater-coolers and heightened clinical awareness are imperative given the consequences of infection.